THE SOUTHERN CAUCASUS: ROAD TO EUROPE - ZURABASHVILI, Georgy (CENTRAL ASIA AND THE CAUCASUS, 2004)
New geopolitical spaces formed by the new sovereign states, some of which are rich in natural resources and others a link in the trans-Asian transportation corridor of strategic im-portance, have filled the expanse formerly occupied by the Soviet Union. The Southern Caucasus is one of the key elements in the newly formed geopolitical expanse, therefore its countries, while dealing with the eco-nomic and political problems of the transition period, had to address another, no less urgent problem of cooperation with the international community. All three post-Soviet South Caucasian states are actively working to create mutually acceptable development patterns applied to their integration into the world community. They are all based on their advantageous geopolitical situation; they all want to create a stable system of international co-operation in order to reach political and economic security. In view of this, their foreign policy priorities are better bilateral mutually advantageous relations, stronger multisided contacts within inter-national, European included, organizations and institutions, and involvement in military, financial, and social programs. Mere statements about their strategic course are not enough to achieve the de-sired aim—radical structural changes which would meet the requirements of the European Union, NATO, and other international organizations are needed. It should be said that the West is still treating the South Caucasian countries with a certain degree of doubt, even though they have already covered part of the road leading to democracy. I do not mean human rights, freedom of the press, or economic liberalization issues. Europe is showing a certain cautiousness when dealing with the South Caucasian states because of the mentality problem. It is no secret that not all Western politicians agree that the Pontic coast is part of the old continent, for them it is a distant, or even alien, part of Europe. The road to the European community has been charted, yet it turned out to be a long and difficult one. At the same time, the local countries, which are seeking stronger sovereignty, political stability, and eco-nomic growth, have no alternatives.